Integrating decolonial theory through signature pedagogies in design education - Botes, Herman (Critical Studies in Teaching and Learning, 2025)
This paper explores the challenges of integrating decolonial theory into design pedagogy within higher education. A case study approach was employed to collect qualitative data from 31 design educators and 23 design students across public and private higher education institutions in South Africa. Based on the findings of the case study, I argue that advancing decolonial design education requires greater engagement with the concepts of belonging and cultural representation, which are recurring themes in the work of Elmarie Costandius. To support this engagement, I propose a matrix that maps conceptions of belonging and cultural representation, as expressed by design educators and students, in relation to Ndlovu-Gatsheni’s (2015) decolonial perspectives and Shreeve’s (2016) signature pedagogies of design. The aim of the paper is to provide a practical tool for design educators seeking to integrate decolonial perspectives in their teaching, with broader implications for other disciplines striving to decolonise their pedagogical practices.